Are water markets a viable proposition in the Lower Mekong Basin? - Reardon-Smith, Kathryn; McCartney, Matthew P.; Rebelo, Lisa-Maria (Edward Elgar Publishing, 2021)
Water markets are a potential approach for reallocating and improving the efficiency of water use in river basins in which water resources are under stress as a consequence of demographic and economic pressures. However, establishing water markets is not easy and to be successful a wide range of context specific criteria, relating to the legal and institutional framework as well as political and economic conditions, must be met. We applied the Water Market Readiness Assessment framework proposed by Wheeler et al. (2017) to investigate whether adequate policy and governance arrangements were in place to enable water markets to effectively operate in the countries of the Lower Mekong River Basin. We identify a number of key gaps and conclude that more conventional regulatory approaches, along with integrated basin planning and management, will likely better serve the communities and environments of the region.